OPERATING EXPENSES FOR LARGE AMERICAN AIR CARRIERS - A. B. Manvelidze (Стратегические решения и риск-менеджмент)
Indicators of prime cost and profitability of passenger traffic on the example of statistics of American Airlines, Delta Airlines and United Airlines. Initial information for researches is accepted according to the financial and statistical analysis of airlines of the. Indicators of cost of transportations and profitability during noticeable reduction of prices of aviation fuel in 2014-2016 are compared. The main attention is paid to the analysis of fleet (park) of planes and changesin separate items of expenditure. The algorithm of calculation of cost of transportations on types of planes according to the statistical account is offered. In calculations it is considered that in air-transport branch of the USA statistical account of factor flight cost on the aerial vehicle types is kept. The share of factor flight cost makes to 50%. Indirect expenses are distributed by a settlement way. Prime cost a chair kilometer on straight lines and indirect items of expenditure of narrow-body planes 737-800/900 and A319/320/321 at range of 2000 km makes from 8,8 to 11 cents. On the ranges, over 2000 km, prime cost decreases to 7,7–8,3 cents.Prime cost a chair kilometer of planes 757-200/300, and widebody 767-300, 777-300, A330-200/300 at range of 3000–5000 km by calculation makes 6,8–7,8 cents for a chair km. Prime cost at ranges over 6000 km makes a chair kilometer of widebody planes 777-200/300, 787-800/900, A330-200/300 from 6,0 to 6,7 cent for a chair km